Power Electronics in Transportation (IEEE Cat. No.04TH8756)
DOI: 10.1109/pet.2004.1393815
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional inverters and Z-source inverter for fuel cell vehicles

Abstract: Abslract: I n this paper, three different inverters: traditional PWM inverter, dc/dc boosted PWM inverter, and Zsource inverter for fuel cell vehicles were investigated. Total switching device power o f each of these inverters was calculated. For purposes of comparison, nu example of the total switching device power, requirement of passive components, efficiency, and the constant power speed ratio of the different inverters powered by the same fuel cell and loaded by the same motor were conducted. This compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
2

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 8 publications
(1 reference statement)
0
102
0
2
Order By: Relevance
“…Comparison of traditional and Z source inverters for fuel cell vehicles is given by shen [8]. The concept of Z source inverter is given by peng [9].…”
Section: Index Terms-power Quality Voltage Sags Dvr Impedance Sourmentioning
confidence: 99%
“…Comparison of traditional and Z source inverters for fuel cell vehicles is given by shen [8]. The concept of Z source inverter is given by peng [9].…”
Section: Index Terms-power Quality Voltage Sags Dvr Impedance Sourmentioning
confidence: 99%
“…10, show that a high gain requires small values of M and that, unfortunately, small values of M lead to large boost which places greater voltage stress on the inverter switches. The total switching device power (SDP) of a traditional PWM inverter, a dc-dc boosted PWM inverter, and a Z-source inverter were calculated and compared showing that the Z-source reduces the total average SDP by 15%, which means lower cost [10]. In the same paper, the motor voltage produced by Z-source inverters, when subjected to the same switch voltage stress as traditional PWM inverters, was 1.55 times greater than that produced by a conventional PWM inverter.…”
Section: + + +mentioning
confidence: 99%
“…The analysis in [4] and [10] considered that during shoot-through the current, which is twice the current through the inductor, passes in parallel through all three legs of the inverter. A paper analyzing PWM operation of a Z-source inverter [11] concluded that under space vector control, for which only one switch could be changed per state, the entire shoot-through current would flow through only one phase, which increases the current stress on the switches as well as the SDP.…”
Section: + + +mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the two switches in the same phase leg can be gated on simultaneously and no dead time is needed, so the output distortion is greatly reduced and the reliability can be improved. Recent research on Z-source inverters mainly focuses on the modulation strategy [2]- [5], the modeling and controller design [6]- [8], the application fields [9]- [11], and other derived Zsource converter topologies [12], [13]. Despite the aforementioned merits, the traditional Z-source inverter topology also shows the following drawbacks: 1) the voltage across Z-source capacitors is no less than input voltage, thus high-voltage capacitors should be used, which may result in larger volume and prove to be cost expensive to the system; 2) it cannot suppress the inrush current and the resonance introduced by Z-source capacitors and inductors at startup, thus causing the voltage and current surge, which, in turn, may destroy the devices.…”
Section: Introductionmentioning
confidence: 99%